2018
DOI: 10.3390/cells7060059
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Secretion and Intercellular Transfer of Mutant Huntingtin

Abstract: The mechanism of intercellular transmission of pathological agents in neurodegenerative diseases has received much recent attention. Huntington’s disease (HD) is caused by a monogenic mutation in the gene encoding Huntingtin (HTT). Mutant HTT (mHTT) harbors a CAG repeat extension which encodes an abnormally long polyglutamine (polyQ) repeat at HTT’s N-terminus. Neuronal pathology in HD is largely due to the toxic gain-of-function by mHTT and its proteolytic products, which forms both nuclear and cytoplasmic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 149 publications
1
17
0
Order By: Relevance
“…While free plasma is a source of mHTT, soluble protein was also detected in all tested immune cells. These cells could have released mHTT into the organs via multiple pathways including through exocytosis [28] or the release of extracellular vesicles [58]. Previous evidence has demonstrated that both exocytosis and extracellular vesicles can contribute to mHTT spreading in HD.…”
Section: Discussionmentioning
confidence: 99%
“…While free plasma is a source of mHTT, soluble protein was also detected in all tested immune cells. These cells could have released mHTT into the organs via multiple pathways including through exocytosis [28] or the release of extracellular vesicles [58]. Previous evidence has demonstrated that both exocytosis and extracellular vesicles can contribute to mHTT spreading in HD.…”
Section: Discussionmentioning
confidence: 99%
“…6 A ). In manifest HD, lysosomal function and autophagy become impaired with aging in association with polyQ expansion of HTT and reduced HTT protein levels (31, 45), resulting in reduced full-length HTT phosphorylation, and mutant HTT exon 1 protein and other autophagy cargos accumulate and aggregate, or may be expelled from the cell for prion-like propagation to neighboring cells (4648). The ensuing cellular stress causes a robust microglial activation (49) and inflammatory pathway induction and accumulation of IKKβ that can no longer activate autophagy (13), resulting in cellular dysfunction and neurodegeneration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HTT, several mechanisms have been proposed, including extracellular vesicles (Tang, 2018) and transneuronal (synaptic) spreading (Pecho‐Vrieseling et al , 2014). Our early work has also shown the intercellular propagation of mHTT through TNTs (Costanzo et al , 2013).…”
Section: An Overview Of Tunneling Nanotubesmentioning
confidence: 99%